Increased anxiety in high-class young athletes in complex sports disciplines - Milashechkina V.V.; Sazonova M.A.; Gernet I.N.; Trotsenko N.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study – is aimed at determining the specific characteristics of anxiety symptoms in highly qualified athletes specializing in complex coordination disciplines. Methods and structure of the study.Aspart of the study, girls aged 12-14years old,engaged in rhythmicgymnastics(n=42)anddiving(n=22) at leastIsportscategory,livingin the centralpart of Russia, wereexamined. The controlgroupconsisted of 48schoolgirls who did notplaysports. The A.Kondashtestadapted by E.I.Rogov(2010), which includesscales of self-assessment andinterpersonal anxiety, was usedtoassess the level of anxiety. The dataobtainedweresubjected to statisticalanalysis. Results and conclusions. The results showed that the most pronounced level of anxiety is observed in 13-year-old female athletes engaged in highly skilled complex sports. In all age groups, the level of anxiety among athletes significantly exceeds that of girls from the control group. Maintaining an optimal level of anxiety is important for achieving high results. Trainers need to take into account the level of anxiety when planning the training process. Parents of young athletes should pay attention to the psychoemotional state of the child in order to prevent the development of serious mental and physiological disorders caused by intense physical exertion.